Xizambi friction-bow music of the Shangana-Tsonga - Johnston, Thomas F. (International Library of African Music, 1970)
Tsonga drums, antelope horns, leg-rattles and whistles are generally used to accompany ritual dancing within the context of two of the three ritual institutions: khomba (puberty school) and mancomane (doctor's ceremonies). Ngoma (circumcision school) is secret and therefore avoids their use. Use may occur, however, within the context of three non-ritual musical institutions: mine dances, beer-drinks and xigubu (boys' drumming school). Two other forms of musical activity - those of work songs and children's songs - rarely employ instruments.
Keywords: South Africa; Music; Tsonga (African people); Ethnomusicology; Musical bow; African Music; Shangana